2017
DOI: 10.1080/10715762.2017.1375486
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH oxidase by apocynin promotes myocardial antioxidant response and prevents isoproterenol-induced myocardial oxidative stress in rats

Abstract: Preventive and/or therapeutic interventions for ischemic heart disease have gained considerable attention worldwide. We investigated the mechanism(s) underlying cardioprotection of apocynin (APO) and whether it attenuates isoproterenol (ISO)-induced myocardial damage in vivo. Thirty-two male Wistar Albino rats were randomised into four groups (n = 8 for each group): Group I (Control); Group II (ISO), ISO was given intraperitoneally (ip) (150 mg/kg/d) daily for 2 consecutive days; Group III (APO + ISO), APO was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 77 publications
0
16
0
1
Order By: Relevance
“…The damaged enzymes, which have the role of electron transferring in the mitochondria, causing the electron transfer to oxygen, in turn resulting in the generation of superoxide, that is, the initial ROS molecule. Also, deterioration of the balance between formation rate of oxidant molecules and antioxidant defenses leads to oxidative stress, which is related to myocardial hyperfunction …”
Section: Discussionmentioning
confidence: 99%
“…The damaged enzymes, which have the role of electron transferring in the mitochondria, causing the electron transfer to oxygen, in turn resulting in the generation of superoxide, that is, the initial ROS molecule. Also, deterioration of the balance between formation rate of oxidant molecules and antioxidant defenses leads to oxidative stress, which is related to myocardial hyperfunction …”
Section: Discussionmentioning
confidence: 99%
“…Of these, Nox2 and Nox4 are highly expressed in the cardiomyocytes mediating both adaptive and maladaptive changes in the heart [8]. Nox activity is reported to be elevated in cardiac dysfunction under different disease states including sepsis, ischemic cardiomyopathy, and heart failure [9, 10]. Increasing evidence has shown that Nox is activated by various stimuli like proinflammatory cytokine TNF- α , endothelin-1 (ET-1), and endotoxin [1113].…”
Section: Introductionmentioning
confidence: 99%
“…NAC, a N -acetyl derivative of L-cysteine and a precursor of the reduced glutathione (GSH), acts as an antioxidant [ 52 ]. Apocynin is a NADPH oxidase (NOX) inhibitor and acts by scavenging the superoxide anion (O 2 −• ), which is generated during the reduction of O 2 by NOX in order to abate the oxidative stress and inflammation [ 53 ]. Curcumin, also known as diferuloylmethane (1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione), is a natural polyphenol found in the rhizome of Curcuma longa (turmeric) and is known to have antioxidant, antiinflammatory, antimicrobial, and antimutagenic or anticancer properties [ 54 ].…”
Section: Discussionmentioning
confidence: 99%